Relationship between the resting heart rate and the extent of coronary artery disease as assessed by myocardial perfusion SPECT (Swiss Medical Weekly, 2012)
AIM: Sustained elevation of resting heart rate (RHR) is thought to promote the initiation and progression of coronary artery disease (CAD). The aim of this paper is to test the hypothesis whether elevated RHR correlates with the presence and the extent of CAD in patients evaluated for CAD. METHODS AND RESULTS: The association between RHR and CAD findings and myocardial perfusion SPECT (MPS) was tested in 1,465 patients. Patients with atrial fibrillation, pacemaker rhythm and treatment with negative chonotropic drugs were excluded. Standard scores for MPS evaluation were used. CAD findings of myocardial ischaemia or scar were present in 408 patients (28%). The prevalence of CAD finding at MPS was not higher among patients with RHR above the median value of 79 bpm compared to patients with lower RHR (28% vs 28%; p = 1.00). The extent of myocardial ischaemia and scar did not increase with higher quartiles of RHR. In contrast, the presence of other established cardiovascular risk factors such as diabetes, male gender, more advanced age and presence of CAD symptoms such as angina and dyspnoea were independent predictors of CAD findings (p